Preparation method of fibrous alumina and fibrous alumina
By conducting neutralization reactions and ammonium salt aging treatments at low temperatures, the surface charge and crystal growth direction of the alumina precursor are controlled, solving the problems of equipment blockage and safety risks in the preparation of fibrous alumina, and realizing efficient and safe production of fibrous alumina.
Patent Information
- Application Number
- CN202511052457.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-12-09
AI Technical Summary
In existing methods for preparing fibrous alumina, the ionic gas generated by the high-temperature decomposition of ammonium salts is prone to condensation, leading to equipment blockage and corrosion, while also affecting the morphology and increasing costs and safety risks.
The neutralization reaction of aluminum sulfate and sodium aluminate solution was carried out under low temperature conditions, combined with ammonium salt aging treatment. The surface charge and crystal growth direction of alumina precursor were regulated by ammonium ions, which inhibited agglomeration and promoted the formation of fibrous structure.
This method enables the preparation of fibrous alumina with high specific surface area and high aspect ratio under non-high pressure conditions, avoiding equipment blockage and corrosion, reducing production costs and safety risks, and outperforming traditional methods.
Smart Images

Figure CN121085294A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of alumina material preparation, and particularly relates to a preparation method of fibrous alumina and fibrous alumina. BACKGROUND
[0002] Fibrous pseudo-boehmite has unique physical and chemical properties such as high specific surface area and large pore volume, and is widely used in the fields of catalyst carriers, adsorbents and the like. The γ-Al2O3 formed by calcining fibrous pseudo-boehmite is an excellent catalyst carrier, catalyst and adsorbent, can effectively load active metals, and has good thermal stability and mechanical strength. Among numerous γ-Al2O3, fibrous alumina is widely used in the fields of catalyst carriers, catalysts and adsorbents due to its numerous active sites and more pore structures.
[0003] However, ammonium salt is mostly used as a modifier in the preparation of fibrous alumina. This preparation method needs to decompose ammonium salt under high-temperature conditions, but the ion gas generated by high-temperature decomposition is easy to condense in a low-temperature region, thereby blocking the equipment, or the ion gas corrodes the equipment through the dynamic transformation of decomposition-condensation; meanwhile, these ions also enter the alumina, affecting the morphology of fibrous alumina. These phenomena undoubtedly increase the preparation cost and safety risk of fibrous alumina. SUMMARY
[0004] The present application provides a preparation method of fibrous alumina and fibrous alumina, to solve the technical problem of how to optimize the morphology characteristics of fibrous alumina.
[0005] In a first aspect, the embodiments of the present application provide a preparation method of fibrous alumina, and the preparation method comprises the following steps:
[0006] neutralizing aluminum sulfate and sodium aluminate solution under a preset temperature condition to obtain a neutralization slurry containing alumina precursor; wherein the preset temperature is ≤70℃;
[0007] aging water, ammonium salt and the neutralization slurry containing alumina precursor to optimize the surface morphology of the alumina precursor through ammonium ions generated by dissociation of the ammonium salt, to obtain an aging slurry containing fibrous alumina;
[0008] filtering and washing the aging slurry containing fibrous alumina to obtain a fibrous alumina product.
[0009] Optionally, the mass m1 of the ammonium salt and the volume V1 of the neutralization slurry satisfy: m1:V1=1:(1 to 4), if the unit of m1 is g, then the unit of V1 is mL.
[0010] Optionally, the kind of the ammonium salt is selected from at least one of the following: ammonium carbonate, ammonium bicarbonate, ammonium chloride, ammonium sulfate and ammonium nitrate.
[0011] Optionally, the volume V2 of the water and the volume V1 of the neutralization slurry satisfy: V2:V1=(0.1 to 1.2):1.
[0012] Optionally, the temperature of the aging treatment is 30°C to 70°C, and the duration of the aging treatment is 6h to 24h.
[0013] Optionally, the aging treatment is carried out in a stirring manner, and the rotation speed of the aging treatment is 50r / min to 300r / min.
[0014] Optionally, the preset temperature is 40°C to 70°C; and / or
[0015] The pH of the neutralization reaction is 4.5 to 7.0.
[0016] Optionally, the alumina content of the sodium aluminate solution is 50g / L to 220g / L, and the alumina content of the aluminum sulfate is 95g / L to 105g / L.
[0017] In a second aspect, the embodiments of the present application provide a fibrous alumina, which is prepared by the preparation method of the first aspect.
[0018] Optionally, the specific surface area of the fibrous alumina is 270m 2 / g to 290m 2 / g, and the aspect ratio of the fibrous alumina is 30 to 50.
[0019] Compared with the prior art, the above technical solutions provided by the embodiments of the present application have the following advantages:
[0020] The preparation method of the fibrous alumina provided by the embodiments of the present application first reacts aluminum sulfate and sodium aluminate under relatively mild conditions, so that a neutralization slurry containing uniformly dispersed alumina precursors can be obtained; then water, an ammonium salt and the neutralization slurry are mixed for aging treatment, so that NH4 + adsorbed on the surface of the alumina precursors in the neutralization slurry can be generated by the dissociation of the ammonium salt during the aging treatment, which can increase the charge density on the surface of the alumina precursors, so as to enhance the electrostatic repulsion between the alumina precursors and inhibit the agglomeration of the alumina precursors. + These NH4 BRIEF DESCRIPTION OF DRAWINGS
[0021] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0022] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a schematic flowchart of a method for preparing fibrous alumina according to an embodiment of this application;
[0024] Figure 2 This is a scanning electron microscope (SEM) schematic diagram of fibrous alumina provided in an embodiment of this application. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0026] The range descriptions used in this application, such as numerical ranges and proportional ranges, include all possible sub-ranges and single numerical values within that range. For example, the range descriptions of "1 to 6" or "1 to 6" cover all sub-ranges (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6) between 1 and 6. Unless otherwise specified, the terms "comprising" and others used herein mean "including but not limited to"; relational terms such as "first" and "second" are used only to distinguish different entities or operations and do not imply an actual order or relationship; "and / or" indicates that multiple situations can exist individually or simultaneously; expressions such as "at least one," "multiple," and "at least one" refer to any combination of the corresponding objects, including combinations of single or multiple objects. The proportional relationships involved in this document, such as mass ratios and molar ratios, should be understood as the correspondence between the first and second terms of a proportional formula, according to the order of description. The raw materials, reagents, instruments, and equipment used herein can all be obtained by purchasing from the market or by existing methods.
[0027] Figure 1 This is a schematic flowchart of a method for preparing fibrous alumina according to an embodiment of this application;
[0028] likeFigure 1 As shown in the embodiments of the present application, a preparation method of fibrous alumina is provided, which comprises:
[0029] S1. Neutralizing aluminum sulfate and sodium aluminate solution under a preset temperature condition to obtain a neutralization slurry containing alumina precursor; wherein the preset temperature is ≤70℃;
[0030] S2. Aging water, ammonium salt and the neutralization slurry containing alumina precursor to optimize the surface morphology of the alumina precursor by ammonium ions produced by the dissociation of the ammonium salt, to obtain an aging slurry containing fibrous alumina;
[0031] S3. Filtering and washing the aging slurry containing fibrous alumina to obtain fibrous alumina product.
[0032] It should be noted that the aging process can be carried out under stirring conditions.
[0033] It should be noted that the preparation method of fibrous alumina provided by the embodiments of the present application optimizes the morphology characteristics of fibrous alumina through aging treatment combined with the complex effect of ammonium salt. The specific mechanism is as follows:
[0034] 1. Charge regulation effect of ammonium ion (NH4 + ):
[0035] Ammonium salt (such as ammonium sulfate, ammonium chloride, etc.) dissociates in water to produce ammonium ion (NH4 + ). The surface of alumina precursor (usually amorphous or microcrystalline aluminum hydroxide gel) particles has a charge (usually positive charge). Therefore, NH4 + ion can be adsorbed on the surface of alumina precursor particles. This adsorption can achieve:
[0036] (1) Reduce the electrostatic repulsion between particles: neutralize or shield part of the charge on the surface of alumina precursor particles, so that alumina precursor particles are more likely to approach each other.
[0037] (2) Promote directional aggregation: under specific aging conditions (temperature, pH, ionic strength), the presence of NH4 + may help guide precursor particles to arrange and connect along a specific crystallographic direction, rather than random agglomeration.
[0038] 2. Optimize the kinetics of crystallization and growth:
[0039] The aging process provides suitable temperature and time for the ripening process of alumina precursor particles to undergo dissolution-recrystallization.
[0040] Additionally, NH4 + adsorption can selectively act on certain crystal faces to inhibit the growth rate of some crystal faces, while relatively promoting the growth of other crystal faces (usually axial direction). Such anisotropic growth is the key to forming one-dimensional fibrous structure. The presence of NH4 + regulates the ion deposition or dissolution rate on different crystal faces, so that the crystal grows into a long and thin fiber first, rather than an equiaxed particle.
[0041] 3. Inhibit densification and agglomeration:
[0042] Without additives or improper conditions, alumina precursor particles are prone to disordered aggregation and densification during the aging process, forming blocky or spherical alumina aggregates.
[0043] At the same time, NH4 + adsorbed on the surface of the particles forms a "barrier" or plays a certain degree of steric hindrance effect, which can reduce the direct contact and hard agglomeration between particles.
[0044] This helps to maintain the relative dispersion state of alumina precursor particles, creating conditions for subsequent directional growth into fibers, and the final product has a higher aspect ratio and clearer fiber morphology.
[0045] 4. Maintain a suitable aging environment:
[0046] The addition of ammonium salt helps to maintain the pH value of the aging slurry in a relatively stable range (usually weakly acidic to neutral). This pH range is crucial for the formation of specific crystal phases and fibrous morphology.
[0047] Ammonium ion itself as an electrolyte also affects the ionic strength of the slurry, which also affects the colloidal stability and crystallization behavior.
[0048] Therefore, the preparation method of fibrous alumina provided by the embodiments of the present application is to introduce ammonium salt for optimization during the aging stage. Ammonium ion (NH4 + ) plays multiple key roles by adsorbing on the surface of alumina precursor particles:
[0049] (1) Regulate the surface charge of alumina precursor particles and reduce electrostatic repulsion;
[0050] (2) Induce directional aggregation and preferential orientation growth, promote one-dimensional structure formation;
[0051] (3) Inhibit disordered agglomeration and densification, maintain structural openness;
[0052] (4) Influence the growth rate of certain crystal faces (inhibit lateral growth, promote axial growth), realize anisotropic growth;
[0053] (5) Assist in maintaining a suitable aging pH environment.
[0054] In summary, the preparation method of fibrous alumina provided by the embodiments of the present application can make the final alumina product present ideal fibrous morphology characteristics (such as high aspect ratio, clear fiber structure, good dispersibility) through the synergistic effect between the process parameters of ammonium salt and aging treatment, rather than ordinary granular or amorphous agglomerates.
[0055] In some optional embodiments, the mass m1 of the ammonium salt and the volume V1 of the neutralized slurry satisfy: m1:V1 = 1:(1 to 4), if the unit of m1 is g, the unit of V1 is mL.
[0056] In these embodiments, the ammonium salt and the neutralized slurry with a mass-volume ratio of 1:(1 to 4) can make the neutralized slurry have sufficient ammonium salt to form NH4 + ions, which can inhibit the agglomeration of the alumina precursor and also selectively regulate the crystal growth direction, so that fibrous alumina with high specific surface area and high aspect ratio can be obtained. +
[0057] The volume V1 of the neutralized slurry can be 1, 1.5, 2.0, 2.5, 3.0, 3.5 or 4.0.
[0058] It should be noted that, in the case of m1:V1 < 1:1, the concentration of NH4 + ions released by the ammonium salt is insufficient, which makes the electrostatic repulsion between the alumina precursor particles insufficient to inhibit the agglomeration of the alumina precursor particles; in the case of m1:V1 > 1:4, the concentration of NH4 + ions released by the ammonium salt is too large, which makes the dispersion degree of the alumina precursor particles too large, which will hinder the directional extension of the fibrous alumina, resulting in short fibers or amorphous structure of the alumina, affecting the purity of the fibrous alumina product.
[0059] In some optional embodiments, the type of the ammonium salt is selected from at least one of the following: ammonium carbonate, ammonium bicarbonate, ammonium chloride, ammonium sulfate and ammonium nitrate.
[0060] In these embodiments, the use of ammonium salt including at least one of ammonium carbonate, ammonium bicarbonate, ammonium chloride, ammonium sulfate and ammonium nitrate can provide sufficient NH4 + ions for the neutralized slurry and ensure that the ammonium salt releases NH4 + The rate of the ions is in a steady state.
[0061] It should be noted that NH4 + The release rate of the ions is unstable (for example, the decomposition of the organic ammonium salt is complex), and the charge density of the surface of the alumina precursor and the growth direction of the crystal cannot be accurately controlled, resulting in loose structure of the fibrous alumina or aggravation of the agglomeration of the alumina precursor.
[0062] In some optional embodiments, the volume V2 of the water and the volume V1 of the neutralized slurry satisfy: V2:V1 = (0.1 to 1.2):1.
[0063] In these embodiments, the volume ratio of the water to the neutralized slurry is (0.1 to 1.2):1, which can improve the dispersibility between the neutralized slurry and the ammonium salt through the dispersion effect of the water, and is conducive to the flow of the materials in the aging process, thereby ensuring the generation of the fibrous alumina.
[0064] The volume V2 of the water can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, or 1.2.
[0065] It should be noted that when the volume V2 of the water and the volume V1 of the neutralized slurry satisfy: V2:V1 < 0.1:1, the volume of the water is small, which makes the viscosity of the mixed system of the water, the ammonium salt, and the neutralized slurry in the aging process too high, and the mixing effect of the three is poor, which makes it difficult to promote the flow of the three in the aging process, resulting in uneven structure of the final fibrous alumina; when the volume V2 of the water and the volume V1 of the neutralized slurry satisfy: V2:V1 > 1.2:1, the volume of the neutralized slurry is too small, which makes the mixed system of the water, the ammonium salt, and the neutralized slurry excessively dispersed, the growth rate of the fibrous alumina is low, the crystallinity of the fibrous alumina product is insufficient, and the specific surface area is low.
[0066] In some optional embodiments, the temperature of the aging process is 30°C to 70°C, and the duration of the aging process is 6h to 24h.
[0067] In these embodiments, the aging process with the temperature of 30°C to 70°C and the duration of 6h to 24h can promote the NH4 + The ions interact with the surface of the alumina precursor, and at the same time, can promote the ripening process of the dissolution-recrystallization of the alumina precursor particles, so as to finally obtain the fibrous alumina product with high aspect ratio and high specific surface area.
[0068] The temperature of the aging process can be 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, or 70°C.
[0069] The duration of the aging treatment can be 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.
[0070] It should be noted that, in the case that the temperature of the aging treatment is less than 30℃, the temperature of the aging treatment is too low to make the alumina precursor particles difficult to complete the directional arrangement, so that the alumina precursor particles are difficult to undergo the ripening process of dissolution-recrystallization, ultimately affecting the aspect ratio and specific surface area of the fibrous alumina; in the case that the temperature of the aging treatment is greater than 70℃, the temperature of the aging treatment is too high, which makes the ripening process of dissolution-recrystallization of the alumina precursor particles excessive, so that the fiber structure of the fibrous alumina is broken, reducing the aspect ratio of the fibrous alumina.
[0071] It should be noted that, in the case that the duration of the aging treatment is less than 6h, the duration of the aging treatment is insufficient, which makes the alumina precursor particles difficult to complete the directional arrangement, so that the alumina precursor particles are difficult to undergo the ripening process of dissolution-recrystallization, ultimately affecting the aspect ratio and specific surface area of the fibrous alumina; in the case that the duration of the aging treatment is greater than 24h, the duration of the aging treatment is too long, which makes the ripening process of dissolution-recrystallization of the alumina precursor particles excessive, so that the fiber structure of the fibrous alumina is broken, reducing the aspect ratio of the fibrous alumina.
[0072] In some optional embodiments, the aging treatment is carried out in a stirring manner, and the rotation speed of the aging treatment is 50r / min to 300r / min.
[0073] In these embodiments, the aging treatment with a rotation speed of 50r / min to 300r / min can make the mixture of water, ammonium salt and neutralization slurry fully mixed, so as to promote the NH4 + ion released by the ammonium salt to fully react with the surface of the alumina precursor, and at the same time, promote the ripening process of dissolution-recrystallization of the alumina precursor particles, so as to ultimately obtain a fibrous alumina product with high aspect ratio and high specific surface area.
[0074] The rotation speed of the aging treatment can be 50r / min, 100r / min, 150r / min, 200r / min, 250r / min or 300r / min.
[0075] It should be noted that in the case of the rotation speed of the aging treatment being less than 50 r / min, the mixing system of water, ammonium salt and neutralization slurry is not uniform, and high concentration distribution of ammonium salt may occur in local areas, so that the distribution of ammonium salt in the mixing system is greatly different, which makes the dispersion performance of the aluminum oxide precursor particles in the aging treatment stage poor, resulting in a low aspect ratio of the final fibrous aluminum oxide; in the case of the rotation speed of the aging treatment being greater than 300 r / min, the shear force of stirring is too large at this time, which makes it difficult for the aluminum oxide precursor particles in the mixing system of water, ammonium salt and neutralization slurry to arrange directionally, destroys the directional extension of fibrous aluminum oxide, and makes a large number of short fibers or broken structures appear in the final fibrous aluminum oxide, significantly reducing the aspect ratio of the fibrous aluminum oxide.
[0076] In some optional embodiments, the preset temperature is 40-70°C; and / or
[0077] The pH of the neutralization reaction is 4.5-7.0.
[0078] In these embodiments, the preset temperature of 40-70°C can reduce the heating load of the aging treatment, so that the aging treatment stage can proceed smoothly to finally obtain fibrous aluminum oxide with a high aspect ratio and a high specific surface area. In addition, the neutralization reaction with a pH of 4.5-7.0 makes the neutralization reaction proceed sufficiently, so that the surface of the aluminum oxide precursor in the neutralization slurry has sufficient electric charge, which is beneficial to the subsequent aging treatment.
[0079] The preset temperature can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C.
[0080] The pH of the neutralization reaction can be 4.5, 5.0, 5.5, 6.0, 6.5 or 7.0.
[0081] It should be noted that in the case of the pH of the neutralization reaction being less than 4.5, the neutralization reaction is incomplete, so that the charge density on the surface of the aluminum oxide precursor particles is insufficient, and the electrostatic repulsion of the aluminum oxide precursor in the subsequent aging treatment stage is weak, so that the aluminum oxide precursor is prone to uncontrollable agglomeration; in the case of the pH of the neutralization reaction being greater than 7.0, the neutralization reaction is too fast, which may cause the formation of disordered colloidal structures in the fibrous aluminum oxide, and these disordered colloidal structures hinder the directional growth of the aluminum oxide precursor along a specific crystal face.
[0082] In some optional embodiments, the aluminum oxide content of the sodium aluminate solution is 50-220 g / L, and the aluminum oxide content of the aluminum sulfate is 95-105 g / L.
[0083] In these embodiments, the sodium aluminate solution with an alumina content of 50 g / L to 220 g / L and the aluminum sulfate with an alumina content of 95 g / L to 105 g / L can provide sufficient aluminum source for the neutralization slurry and ensure uniform dispersion of the alumina precursor, thus facilitating subsequent aging treatment.
[0084] The alumina content of the sodium aluminate solution can be 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 150 g / L, 200 g / L, or 220 g / L.
[0085] The alumina content of the aluminum sulfate can be 95 g / L, 96 g / L, 97 g / L, 98 g / L, 99 g / L, 100 g / L, 101 g / L, 102 g / L, 103 g / L, 104 g / L, or 105 g / L.
[0086] It should be noted that, when the alumina content of the sodium aluminate solution is less than 50 g / L or the alumina content of the aluminum sulfate is less than 95 g / L, the aluminum source of the neutralization slurry will be insufficient, which will affect the neutralization reaction and reduce the yield of the alumina precursor, resulting in low crystallinity of the final fibrous alumina; when the alumina content of the sodium aluminate solution is greater than 220 g / L or the alumina content of the aluminum sulfate is greater than 105 g / L, the viscosity of the neutralization slurry will be too large, and the neutralization reaction will be in a violent state, which will cause the alumina precursor particles to rapidly agglomerate and make it difficult to form fibrous alumina with uniform fiber structure distribution.
[0087] Figure 2 An example of a scanning electron microscope image of the fibrous alumina provided by the embodiments of the present application is shown;
[0088] Based on a general inventive concept, as Figure 2 shown, the embodiments of the present application provide a fibrous alumina prepared by the preparation method.
[0089] The fibrous alumina is prepared based on the above method, and the specific steps of the method can be referred to the above embodiments. Since the method uses part or all of the technical solutions of the above embodiments, it at least has all the beneficial effects brought by the technical solutions of the above embodiments, which will not be repeated here.
[0090] In some optional embodiments, the specific surface area of the fibrous alumina is 270 m 2 / g to 290 m 2 / g, and the aspect ratio of the fibrous alumina is 30 to 50.
[0091] In these embodiments, the specific surface area of the fibrous alumina is 270 m 2270m 2 / g and the fibrous alumina has an aspect ratio of 30 to 50, which indicates that the method provided by the embodiments of the present application can be used to prepare fibrous alumina products with high specific surface area and high aspect ratio.
[0092] The fibrous alumina has a specific surface area of 270m 2 / g, 275m 2 / g, 280m 2 / g, 285m 2 / g or 290m 2 / g.
[0093] The fibrous alumina has an aspect ratio of 30, 35, 40, 45 or 50.
[0094] The present application will be further described in conjunction with specific embodiments. The experimental methods in the following embodiments are not specified, and are generally determined according to national standards / industry standards; if there is no corresponding national standard / industry standard, the general international standard, conventional conditions or the conditions suggested by the manufacturer are used.
[0095] Embodiment 1
[0096] As shown in the following, a method for preparing fibrous alumina comprises: Figure 1
[0097] S1. Neutralizing aluminum sulfate and sodium aluminate solution under a preset temperature condition to obtain a neutralization slurry containing alumina precursor; wherein the preset temperature is ≤70℃;
[0098] S2. Aging the water, ammonium salt and neutralization slurry containing alumina precursor to optimize the surface morphology of the alumina precursor by ammonium ions produced by the dissociation of the ammonium salt, to obtain an aging slurry containing fibrous alumina;
[0099] S3. Filtering and washing the aging slurry containing fibrous alumina to obtain fibrous alumina products.
[0100] The mass m1 of the ammonium salt and the volume V1 of the neutralization slurry satisfy: m1:V1=100g:100mL, if the unit of m1 is g, then the unit of V1 is mL.
[0101] The type of ammonium salt is ammonium carbonate.
[0102] The volume V2 of water and the volume V1 of the neutralization slurry satisfy: V2:V1=50mL:100mL.
[0103] The aging temperature is 50℃, and the duration of the aging treatment is 12h.
[0104] The aging treatment is performed in a stirring manner, and the rotation speed of the aging treatment is 100 r / min.
[0105] The preset temperature is 55℃.
[0106] The pH of the neutralization reaction is 6.5.
[0107] The alumina content of the sodium aluminate solution is 50 g / L, and the alumina content of the aluminum sulfate is 95 g / L.
[0108] Example 2
[0109] Compared with Example 1, the differences of the present example are as follows, and the rest are the same:
[0110] The mass m1 of the ammonium salt and the volume V1 of the neutralization slurry satisfy: m1:V1=150 g:120 mL, if the unit of m1 is g, then the unit of V1 is mL.
[0111] The type of the ammonium salt is ammonium bicarbonate.
[0112] The volume V2 of water and the volume V1 of the neutralization slurry satisfy: V2:V1=30 mL:120 mL.
[0113] The temperature of the aging treatment is 40℃, and the duration of the aging treatment is 18 h.
[0114] The rotation speed of the aging treatment is 150 r / min.
[0115] The preset temperature is 65℃.
[0116] The pH of the neutralization reaction is 4.8.
[0117] The alumina content of the sodium aluminate solution is 75 g / L, and the alumina content of the aluminum sulfate is 100 g / L.
[0118] Example 3
[0119] Compared with Example 1, the differences of the present example are as follows, and the rest are the same:
[0120] The mass m1 of the ammonium salt and the volume V1 of the neutralization slurry satisfy: m1:V1=60 g:80 mL, if the unit of m1 is g, then the unit of V1 is mL.
[0121] The type of the ammonium salt is ammonium chloride.
[0122] The volume V2 of water and the volume V1 of the neutralization slurry satisfy: V2:V1=80 mL:80 mL.
[0123] The temperature of the aging treatment is 60℃, and the duration of the aging treatment is 10 h.
[0124] The aging treatment is performed in a stirring manner, and the rotation speed of the aging treatment is 200 r / min.
[0125] The preset temperature is 70℃.
[0126] The pH of the neutralization reaction is 5.5.
[0127] The alumina content of the sodium aluminate solution is 90 g / L, and the alumina content of the aluminum sulfate is 105 g / L.
[0128] Example 4
[0129] Compared with Example 1, the differences of the present example are as follows, and the rest are the same:
[0130] The mass m1 of the ammonium salt and the volume V1 of the neutralization slurry satisfy: m1:V1=90g:110mL, if the unit of m1 is g, then the unit of V1 is mL.
[0131] The type of the ammonium salt is ammonium sulfate.
[0132] The volume V2 of water and the volume V1 of the neutralization slurry satisfy: V2:V1=40mL:110mL.
[0133] The temperature of the aging treatment is 70℃, and the duration of the aging treatment is 15h.
[0134] The rotation speed of the aging treatment is 80 r / min.
[0135] The preset temperature is 50℃.
[0136] The pH of the neutralization reaction is 7.0.
[0137] The alumina content of the sodium aluminate solution is 105 g / L, and the alumina content of the aluminum sulfate is 95 g / L.
[0138] Example 5
[0139] Compared with Example 1, the differences of the present example are as follows, and the rest are the same:
[0140] The mass m1 of the ammonium salt and the volume V1 of the neutralization slurry satisfy: m1:V1=120g:90mL, if the unit of m1 is g, then the unit of V1 is mL.
[0141] The type of the ammonium salt is ammonium nitrate.
[0142] The volume V2 of water and the volume V1 of the neutralization slurry satisfy: V2:V1=60mL:90mL.
[0143] The temperature of the aging treatment is 35℃, and the duration of the aging treatment is 20h.
[0144] The rotation speed of the aging treatment is 250 r / min.
[0145] The preset temperature is 60℃.
[0146] The pH of the neutralization reaction is 5.0.
[0147] The alumina content of the sodium aluminate solution is 150 g / L, and the alumina content of the aluminum sulfate is 100 g / L.
[0148] Example 6
[0149] Compared with Example 1, the differences of the present example are as follows, and the rest are the same:
[0150] The mass m1 of the ammonium salt and the volume V1 of the neutralization slurry satisfy: m1:V1 = 80 g:100 mL, if the unit of m1 is g, then the unit of V1 is mL.
[0151] The type of the ammonium salt is ammonium sulfate.
[0152] The volume V2 of water and the volume V1 of the neutralization slurry satisfy: V2:V1 = 70 mL:100 mL.
[0153] The temperature of the aging treatment is 45℃, and the duration of the aging treatment is 16 h.
[0154] The rotation speed of the aging treatment is 120 r / min.
[0155] The preset temperature is 70℃.
[0156] The pH of the neutralization reaction is 7.0.
[0157] The alumina content of the sodium aluminate solution is 190 g / L, and the alumina content of the aluminum sulfate is 100 g / L.
[0158] Comparative Example 1
[0159] Compared with Example 1, the differences of the present example are as follows, and the rest are the same:
[0160] The mass m1 of the ammonium salt and the volume V1 of the neutralization slurry satisfy: m1:V1 = 80 g:100 mL, if the unit of m1 is g, then the unit of V1 is mL.
[0161] The type of the ammonium salt is ammonium sulfate.
[0162] The volume V2 of water and the volume V1 of the neutralization slurry satisfy: V2:V1 = 70 mL:100 mL.
[0163] The temperature of the aging treatment is 180℃, and the duration of the aging treatment is 16 h.
[0164] The rotation speed of the aging treatment is 120 r / min.
[0165] The preset temperature is 10℃.
[0166] The pH of the neutralization reaction is 7.0.
[0167] The alumina content of the sodium aluminate solution is 190 g / L, and the alumina content of the aluminum sulfate is 100 g / L.
[0168] Comparative Example 2
[0169] The differences between the comparative example and Example 1 are as follows, and the rest are the same:
[0170] The temperature of the aging treatment is 20℃.
[0171] Comparative Example 3
[0172] The differences between the comparative example and Example 1 are as follows, and the rest are the same:
[0173] The mass m1 of the ammonium salt and the volume V1 of the neutralization slurry satisfy: m1:V1=20g:100mL.
[0174] Comparative Example 4
[0175] The differences between the comparative example and Example 1 are as follows, and the rest are the same:
[0176] The mass m1 of the ammonium salt and the volume V1 of the neutralization slurry satisfy: m1:V1=120g:100mL.
[0177] Related experiments and effect data:
[0178] The alumina products of each example and comparative example are counted respectively, and the appearance characteristic data are shown in Table 1.
[0179] Table 1 Appearance characteristic parameters of alumina products of each example and comparative example
[0180]
[0181]
[0182] As can be seen from Table 1, the preparation method of fibrous alumina provided in the embodiments of the present application can make the final alumina product exhibit ideal fibrous appearance characteristics through the synergistic effect between the process parameters of the ammonium salt and the aging treatment. Finally, fibrous alumina products with a specific surface area of 270 m 2 / g or more, an average aspect ratio of 30:1 or more, and a fiber length of 1.5 μm or more can be obtained.
[0183] In summary, the embodiment of the present application provides a preparation method of fibrous alumina, which realizes the ideal fibrous morphology of the final alumina product through the synergistic effect between the ammonium salt and the process parameters of the aging treatment.
[0184] In addition, the embodiment of the present application provides a preparation method of fibrous alumina, which first performs a neutralization reaction under a relatively mild preset temperature condition, and then uses the synergistic effect of the dynamic process parameters (including pH value, ammonium salt type, stirring rate, temperature and time, etc.) of the ammonium salt and the aging treatment process, and simultaneously controls the charge control and the guiding mechanism of the crystal growth direction based on the surface of the alumina precursor, to effectively inhibit the agglomeration of the fibrous alumina precursor particles and promote the directional extension of the fibrous structure, so as to realize the efficient synthesis of the fibrous alumina product under non-high pressure conditions.
[0185] In addition, the embodiment of the present application provides a preparation method of fibrous alumina, which realizes the ideal fibrous morphology of the final alumina product through the synergistic effect between the ammonium salt and the process parameters of the aging treatment.
[0186] In addition, the embodiment of the present application provides a preparation method of fibrous alumina, which realizes the ideal fibrous morphology of the final alumina product through the synergistic effect between the ammonium salt and the process parameters of the aging treatment. 2 2 In addition, the embodiment of the present application provides a preparation method of fibrous alumina, which realizes the ideal fibrous morphology of the final alumina product through the synergistic effect between the ammonium salt and the process parameters of the aging treatment.
[0187] The above merely describes the specific embodiments of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features of the present application.
Claims
1. A method for preparing fibrous alumina, the method comprising: Under preset temperature conditions, aluminum sulfate and sodium aluminate solutions are neutralized to obtain a neutralized slurry containing an alumina precursor; wherein the preset temperature is ≤70℃. The neutralized slurry containing water, ammonium salt, and alumina precursor is aged to optimize the surface morphology of the alumina precursor through ammonium ions generated by the dissociation of the ammonium salt, resulting in an aged slurry containing fibrous alumina. The aging slurry containing fibrous alumina is filtered and washed to obtain the fibrous alumina product.
2. The preparation method according to claim 1, characterized in that, The mass m1 of the ammonium salt and the volume V1 of the neutralizing slurry satisfy the following condition: m1:V1=1:(1 to 4). If the unit of m1 is g, then the unit of V1 is mL.
3. The preparation method according to claim 1 or 2, characterized in that, The ammonium salt is selected from at least one of the following: ammonium carbonate, ammonium bicarbonate, ammonium chloride, ammonium sulfate, and ammonium nitrate.
4. The preparation method according to claim 1, characterized in that, The volume V2 of the water and the volume V1 of the neutralizing slurry satisfy the following condition: V2:V1 = (0.1 to 1.2):
1.
5. The preparation method according to claim 1, characterized in that, The aging treatment is performed at a temperature of 30°C to 70°C for a duration of 6 hours to 24 hours.
6. The preparation method according to claim 1 or 5, characterized in that, The aging process is carried out by stirring, and the rotation speed of the aging process is from 50 r / min to 300 r / min.
7. The preparation method according to claim 1, characterized in that, The preset temperature is 40°C to 70°C; and / or The pH of the neutralization reaction is between 4.5 and 7.
0.
8. The preparation method according to claim 1, characterized in that, The sodium aluminate solution has an alumina content of 50 g / L to 220 g / L, and the aluminum sulfate has an alumina content of 95 g / L to 105 g / L.
9. A fibrous alumina, wherein the fibrous alumina is prepared by the preparation method according to any one of claims 1 to 8.
10. The fibrous alumina according to claim 9, characterized in that, The specific surface area of the fibrous alumina is 270 m². 2 / g to 290m 2 / g, wherein the aspect ratio of the fibrous alumina is 30 to 50.